William$1 (Bthe outlaws - Crompton, Richmal, 1890-1969; Henry, Thomas, 1879-1962 (Salt Lake City, UT : Project Gutenberg, 2023)
"William$1 (Bthe Outlaw" by Richmal Crompton is a children's novel written in the early 20th century. The book follows the mischievous adventures of William Brown and his friends, a group known as the Outlaws, as they navigate their childhood while often finding themselves in trouble for their antics. The stories typically revolve around themes of friendship, rebellion against authority, and the imaginative escapades of young boys. At the start of the novel, the Outlaws, led by the spirited William, are reluctant to go to school on a sunny afternoon. Instead, they dream of becoming "real Outlaws," imagining a life in the woods free from school and adult constraints. However, their plan to escape leads to humorous challenges, including an encounter with various authority figures from their school and a misunderstanding involving a ferocious man and an unexpected lecture. The first chapter sets the tone for the light-hearted adventure and chaos that are to follow, establishing William as a character filled with infectious optimism and a knack for getting into trouble. (This is an automatically generated summary.)s
William--the outlaw -- The terrible magician -- Georgie and the outlaws -- William and the white elephants -- The stolen whistle -- William finds a job -- William's busy day.
Wikipedia page about this book: https://en.wikipedia.org/wiki/William_the_Outlaw
Release date is 2023-05-10
Alan, deaurider and the Online Distributed Proofreading Team at https://www.pgdp.net
Keywords: Children's stories, English; Humorous stories, English; Boys -- Juvenile fiction; William (Fictitious character from Crompton) -- Juvenile fiction